Balancing AI and EQ in Customer Experience: Achieving Balance between AI and Emotional Empathy in Customer Experience (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Purpose This review paper attempts to restructure the belief of organizations, with reconnaissance todesigning a business process on customer experiences. The objective is to identify the equilibrium ascustomer experience is dependent on AI, emotional empathy and connect. We want a roadmap towardsappropriate mechanism, maximizing speed, frequency, and relevance favorable to customer experiences.We took experience journey as a prominent pillar of hospitality and Retail (Real Estate). We are validating,digital process acquired, tested and affirms client expectations Are we matching up to the desired treads ofwish list of the brand The first step is to identify the AI, VOC, COE, software solution automation incustomer service, showing that a value of the emotional connect aims to upgrade CLC. The customerinteraction with the employees bestows instead of burdening the process. In the questionnaire, thefeedbacks, surveys, outcome helped us curb the corners, that indicate optimization of CSAT, CES andAHT.Findings We all agree digital transformation is no longer optional. Collated customer intelligence andemotional empathy insights, illustrate this as an organic method. We must encapsulate the emotions.Digitization diagnoses the statistics and numbers for the where, how and when factor. The emotional pathdiscerns the way customers feel, think, and passively collect the emotions evoked at any touchpoint.Adding the „Feel‟ elements to what we record in customers and employees voice, indicates the influenceson thefuture of their loyalty.Contribution The study facilitates the role of a CX strategist who inscribes a CX concept. Proficientvisionary does not bring a „one fit for all‟ customer experience. The IT team designs the UXUI journeypoints through a sensitive, sanitized sympathetic, classified architecture. CX strategist provides empiricalsupport to the customers and brands, exhibiting true character. This has determined an obvious 360-degreeoutlook. It has also identified the trilateral bottom line‟.Practical implications A integrated, open API in the software, wins the gigantic purpose. while it iscapable to perform its magnum objective. Integration in the existing software creates continuity,efficiency and harmony with ERP or POS. Simplifying the obscure flows at the backend and smooth frontpoint utilization. Customized tools, designed industry specific, bring a bling to the performance inoperation flows. Like real estate, health, travel, all have custom designed CRM software. This caters todata collection and security. Assessing, reading, analysing data from the collection points, insure safetyand security of the data. The data validation collected at various points witness the customer behaviorpatterns in true sense.They can channelize the CX in the circuit of global marketing, international conventions, combined with aband width of large contributions from self-endorsed services and instances‟.Research limitations The in-depth, ongitudinal study, exposed deep-rooted factors and inferences.Brands start with good intent but loose consistent journey. Feeling heavy on pocket, time consuming,optional. Companies exhaust and renounce the customer‟s journey. Breaking the trust in CX. This iscoerced damage, very challenging for the survey and research and any promise is tough to convince. Onceyou raise hopes, announcing sudden closure of your new CX policies, snaps at all the channels in oneshot. The VOC of such customer reflects disappointment due to this impulsive shift, displaying disloyaltyof the principals.